2020
DOI: 10.3390/su12208582
|View full text |Cite
|
Sign up to set email alerts
|

The Water-Energy-Food Nexus as an Adaptation Strategy for Achieving Sustainable Livelihoods at a Local Level

Abstract: The imbalance between resource availability and population increase requires transformative approaches to inform policy, decision-making and practice on coherent adaptation strategies for improved livelihoods and resilient communities. Nexus approaches are built on an understanding that natural processes do not operate in isolation within a system; hence, an emergent challenge in one unit obviously disturbs the whole system. This study applied an integrated water-energy-food (WEF) nexus analytical model to hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…As diseases do not know political boundaries, interventions should also consider the transboundary nature of water and other resources as planning and management of both surface and groundwater resources may lead to more resilient systems and increase regional storage [42,43]. Enhancing water security at the regional level has many benefits that include promoting environmental and human health, increasing the resilience of communities to climate change, supporting livelihoods, food security, and economic productivity [44,45].…”
Section: Mirroring Into the Futurementioning
confidence: 99%
“…As diseases do not know political boundaries, interventions should also consider the transboundary nature of water and other resources as planning and management of both surface and groundwater resources may lead to more resilient systems and increase regional storage [42,43]. Enhancing water security at the regional level has many benefits that include promoting environmental and human health, increasing the resilience of communities to climate change, supporting livelihoods, food security, and economic productivity [44,45].…”
Section: Mirroring Into the Futurementioning
confidence: 99%
“…The results showed that the attention and reform of rural livelihoods led to the extension of the farmland scale. In a word, an integrated model of the WEF nexus can be applied to comprehensively analyse the state of resources at the local level, which provided guidelines for improving the livelihoods of resource-poor rural communities [38].…”
Section: External Research Of the Wef Nexusmentioning
confidence: 99%
“…These connections indicate the intricate relationships be tween the three sectors, whereby any transformation on any of the three should not b implemented independently of the other two. Previous studies have also shown the broad interlinkages between socio-economi development and human and environmental health [27,38]. How humankind uses lan directly impacts ecosystem services and has implications for future land use options [39 Therefore, the broad interlinkages in the three sectors require a holistic approach to ensur sustainable rural development.…”
Section: Transformative Processes Towards a Sustainable Land Redistri...mentioning
confidence: 99%
“…Based on this question, we developed a framework based on nexus planning to guide policy and support decision-making in developing coherent strategies that lead to sustainable implementation of land reforms without compromising national water and food security. Nexus planning was a preferred approach to develop the land redistribution framework as it can integrate distinct but interlinked sectors of land, water, environment and food [27,28]. The study focused on South Africa, a country where land and water inequalities remain contentious.…”
Section: Introductionmentioning
confidence: 99%